The Effect Of The Think Pair Share Learning Model To Improve PKN Learning Outcomes Of Grade III Students - Butar-butar, Jesica; Lumbantobing, Minar T.; Thesalonika, Emelda (CV Putra Publisher, 2025)
This study aims to determine the effect of the Think Pair Share learning model on the learning outcomes of third-grade students in Elementary School 124398 Pematang Siantar. This study uses a quantitative approach with the One Group Pretest-Postest pre-experimental design method. This study was conducted at Elementary School 124398 Pematang Siantar. Based on data analysis, a significant increase in student learning outcomes was obtained after the implementation of the Think Pair Share learning model. This is indicated by an increase in the average student score from the Pretest of 47.48 to 85.74 on the posttest. So, after using the Think Pair Share learning model, the learning outcomes obtained were higher compared to before using the Think Pair Share learning model. Furthermore, the value resulting from the Normality test is 0.323. This test is used to determine whether the data is normally distributed or not. Then the t-test can be seen t_(hitung>) t_(tabel ), with a significance level of 0.05. So the results show that t_(hitung>) = 18.21 fromt_(tabel )= 1.714 which means there is a significant difference. This means that there is an Effect of the Think Pair Share Learning Model to Improve Civics Learning Outcomes of Grade III Students of SD Negeri 124398 Pematang Siantar in the 2025/2026 Academic Year